2013
DOI: 10.1136/jclinpath-2013-201692
|View full text |Cite
|
Sign up to set email alerts
|

The role of NDRG1 in the pathology and potential treatment of human cancers

Abstract: N-myc downstream regulated gene 1 (NDRG1) has been well characterised to act as a metastatic suppressor in a number of human cancers. It has also been implicated to have a significant function in a number of physiological processes such as cellular differentiation and cell cycle. In this review, we discuss the role of NDRG1 in cancer pathology. NDRG1 was observed to be downregulated in the majority of cancers. Moreover, the expression of NDRG1 was found to be significantly lower in neoplastic tissues as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 79 publications
(95 reference statements)
1
87
0
Order By: Relevance
“…The N-myc downstream-regulated gene 1 protein (NDRG1) was present in 18.8 fold higher amounts in spheroids. NDRG1 has been shown to be a metastatic suppressor for several human cancers and has been implicated in several physiological processes including cellular differentiation and the G 0 /G 1 arrest [45]. Similarly, the ras GTPase-activating-like protein IQGAP2 was strongly increased (5.53).…”
Section: Resultsmentioning
confidence: 99%
“…The N-myc downstream-regulated gene 1 protein (NDRG1) was present in 18.8 fold higher amounts in spheroids. NDRG1 has been shown to be a metastatic suppressor for several human cancers and has been implicated in several physiological processes including cellular differentiation and the G 0 /G 1 arrest [45]. Similarly, the ras GTPase-activating-like protein IQGAP2 was strongly increased (5.53).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of studies have shown the important role of NDRG1 in inhibiting cancer cell metastasis (Kovacevic and Richardson, 2006;Liu et al, 2011b;Chen et al, 2012;Liu et al, 2012b;Bae et al, 2013;Mao et al, 2013b;Sun et al, 2013a). However, complete understanding of its mechanism of action remains an important research goal.…”
Section: Discussionmentioning
confidence: 99%
“…This included an examination of FRAT1 expression (Hagen et al, 2006;MacDonald et al, 2009;Verheyen and Gottardi, 2010;Bae et al, 2013) and GSK3b phosphorylation (at Ser9 and Tyr216; Wu and Pan, 2010), and an assessment of the expression of CK1 (Stamos and Weis, 2013), PP1 (Stamos and Weis, 2013) and PP2A (Ikeda et al, 2000).…”
Section: Ndrg1 Inhibits B-catenin Phosphorylation At Ser33/37 and Thr41mentioning
confidence: 99%
See 1 more Smart Citation
“…To further characterize the functional effects of these two missense variants in NDRG1 , cell transfection studies were performed in this report. It is well known that NDRG1 is widely expressed in a variety of human tissues and was first regarded as a metastatic suppressor in a number of human cancers (Bae et al., ). NDRG1 is located in the cytoplasm and nucleus and is related to vesicle transport (Askautrud et al., ; Berger et al., ; Bucci, Bakke & Progida, ; King et al., ).…”
Section: Discussionmentioning
confidence: 99%